Active TB screening among homeless people attending soup kitchens in Verona (Italy) - Tralli, V.; Bertoni, C.; Colucci, L.; Postiglione, C.; Valsecchi, M.; Tocco-Tussardi, I.; Tardivo, S.; Majori, S.; Moretti, F. (Annali di Igiene Medicina Preventiva e di Comunità, 2025)
Background. The hard-to-reach populations, including the homeless, are particularly vulnerable to the development of active tuberculosis. According to the World Health Organization, tuberculosis rates among the homeless in industrialized Countries are up to 20 times higher if compared with the general population, representing a relevant public health problem. The aim of our study was to describe the results of an active tuberculosis screening applied in order to find out suspected active TB cases among the homeless in Verona. Methods. As part of a partnership between the non-profit association Medici per la Pace and one of the Local Health Units of Veneto Region (ULSS 9 Scaligera) in 2018, a tuberculosis screening, based on thoracic radiographs, was offered to the homeless guests of two Verona’s soup kitchens. Results. The studied population included 139 people, and three cases of suspected active tuberculosis, all in males, were observed. Among these, two received a diagnostic confirmation of active tuberculosis (a prevalence of 1.44% - CI: 0,17 – 5,1). Moreover, radiographic patterns of tuberculosis aftermaths were found in six additional subjects. Conclusions. Interventions specifically dedicated to hard-to-reach populations, can be useful in identifying tuberculosis active cases and controlling the disease in low tuberculosis burden countries. In particular, the active research of subjects, the screening carried out with mobile X-ray, and also the constant caring of the patients with active disease, could be the right method to keep under control this relevant public health problem.